The National Cancer Aid monitoring (NCAM-online) of ultraviolet radiation risk and protection behavior: a population-based observational trend study with four annual online survey waves - Katharina Diehl; Eckhard W. Breitbart; Yvonne de Buhr; Tatiana Görig (BMC, 2024)
Abstract Background Ultraviolet (UV) radiation is the most important risk factor for skin cancer development. Sunlight is the main source of UV radiation in the general population. In addition, tanning beds are a source of artificial UV radiation. Since the incidence of skin cancer is increasing worldwide, it is necessary to monitor UV-related risk behaviors such as intentional indoor and outdoor tanning, as well as sun protection behavior in the general population and specific subgroups and settings. This is the aim of the National Cancer Aid Monitoring online (NCAM-online), a continuation and further development of the NCAM. Methods The NCAM-online is a longitudinal trend study consisting of four annual survey waves. Each year, 4,000 individuals aged 16-65 years living in Germany will be surveyed using online questionnaires. Each year, intentional indoor and outdoor tanning will be assessed. In addition, varying specific topics regarding skin cancer prevention, such as the utilization of skin cancer screening, will be addressed in the questionnaires. Discussion The findings of the NCAM-online will provide an important basis for the German Cancer Aid and Working Group on Dermatologic Prevention (Arbeitsgemeinschaft Dermatologische Prävention, ADP) to develop targeted prevention campaigns and projects aimed at preventing skin cancer. The explorative nature of the NCAM-online allows for the identification of new potential starting points for prevention and education. In addition, the longitudinal design allows for a description of the trend in the prevalence of intentional tanning. For tanning bed use, representative trend data from 2012 are available for Germany, to which NCAM-online will add annual data until 2027.